If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k(11 + -1k) + (12 + -1k + 1) = (k + 1)(11 + -1k + 1) (11 * k + -1k * k) + (12 + -1k + 1) = (k + 1)(11 + -1k + 1) (11k + -1k2) + (12 + -1k + 1) = (k + 1)(11 + -1k + 1) Reorder the terms: 11k + -1k2 + (12 + 1 + -1k) = (k + 1)(11 + -1k + 1) Combine like terms: 12 + 1 = 13 11k + -1k2 + (13 + -1k) = (k + 1)(11 + -1k + 1) Remove parenthesis around (13 + -1k) 11k + -1k2 + 13 + -1k = (k + 1)(11 + -1k + 1) Reorder the terms: 13 + 11k + -1k + -1k2 = (k + 1)(11 + -1k + 1) Combine like terms: 11k + -1k = 10k 13 + 10k + -1k2 = (k + 1)(11 + -1k + 1) Reorder the terms: 13 + 10k + -1k2 = (1 + k)(11 + -1k + 1) Reorder the terms: 13 + 10k + -1k2 = (1 + k)(11 + 1 + -1k) Combine like terms: 11 + 1 = 12 13 + 10k + -1k2 = (1 + k)(12 + -1k) Multiply (1 + k) * (12 + -1k) 13 + 10k + -1k2 = (1(12 + -1k) + k(12 + -1k)) 13 + 10k + -1k2 = ((12 * 1 + -1k * 1) + k(12 + -1k)) 13 + 10k + -1k2 = ((12 + -1k) + k(12 + -1k)) 13 + 10k + -1k2 = (12 + -1k + (12 * k + -1k * k)) 13 + 10k + -1k2 = (12 + -1k + (12k + -1k2)) Combine like terms: -1k + 12k = 11k 13 + 10k + -1k2 = (12 + 11k + -1k2) Add 'k2' to each side of the equation. 13 + 10k + -1k2 + k2 = 12 + 11k + -1k2 + k2 Combine like terms: -1k2 + k2 = 0 13 + 10k + 0 = 12 + 11k + -1k2 + k2 13 + 10k = 12 + 11k + -1k2 + k2 Combine like terms: -1k2 + k2 = 0 13 + 10k = 12 + 11k + 0 13 + 10k = 12 + 11k Solving 13 + 10k = 12 + 11k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-11k' to each side of the equation. 13 + 10k + -11k = 12 + 11k + -11k Combine like terms: 10k + -11k = -1k 13 + -1k = 12 + 11k + -11k Combine like terms: 11k + -11k = 0 13 + -1k = 12 + 0 13 + -1k = 12 Add '-13' to each side of the equation. 13 + -13 + -1k = 12 + -13 Combine like terms: 13 + -13 = 0 0 + -1k = 12 + -13 -1k = 12 + -13 Combine like terms: 12 + -13 = -1 -1k = -1 Divide each side by '-1'. k = 1 Simplifying k = 1
| 7x-0.96=6(x-0.67) | | 5x+2.9=6x+2.8 | | -6x+3.2=-3x+4.4 | | 5x+1.2=x+3.6 | | 5x-0.1=3x | | -2(x-1)=14 | | 16X^2=25 | | -7(5-4x)=189 | | 3x+0.6=x | | 35=5 | | 2x^2+1x-3=0 | | 35=-5 | | 4(x-6)=-52 | | 2(x+2)=-14 | | 3(x+9)=45 | | 2(x+2)=-8 | | 81x^2=25 | | 5(x-3)=-50 | | 3(x-8)=-45 | | 9x^2=16 | | 5(x+5)=40 | | 25x^2=36 | | 3(x-9)=-24 | | 5(x+7)=50 | | 15x-3(x+6)=6 | | 4.2(x+3)=27 | | -9x+2.2=-3x+7.0 | | 1.333w-12=.666w | | -5x+2.5=-3x+1.1 | | -3x-3.9=-7x-2.7 | | x^2(9x+5)(9x-5)=0 | | 8x-1.2=-9x+14.1 |